Взаимодействие железных порошков различной дисперсности с плазмой крови человека - Бошицкая, Н.В.; Иващенко, Е.А.; Уварова, И.В.; Проценко, Л.С.; Будилина, О.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The interaction between pure iron powders, which possess different sizes of particles and different surface morphologies, and human blood plasma is studied.